The impacts of task complexity, overconfidence, confirmation bias, customer influence, and anchoring on variations in real estate valuations - Lee, Chun-Chang; Lee, Hsueh-Yung; Yeh, Wen-Chih; Yu, Zheng (International Journal of Strategic Property Management, 2022)
Real estate valuation relies on real estate appraisers’ accurate assessments, which reflects the need to improve the objectivity of the valuation process. From the perspective of behavioral economics, appraisers are prone to numerous behavioral conflicts that could result in variations in their valuations. This study investigates the impacts of task complexity, overconfidence, confirmation bias, client influence, and anchoring on variations in real estate valuations. An online questionnaire was administered to 272 members of the Taiwan Real Estate Appraisers Association LINE group. Structural equation modeling was employed for analysis. A total of 150 valid responses were collected, yielding a valid response rate of 55.15%. The empirical results revealed that cognitive bias and client influence have significant and positive impacts on anchoring. Task complexity, overconfidence, and customer influence have significant and positive impacts on valuation variation. In addition to being the first study to explore the relationship between task complexity and valuation variation, this study also explored unconventional issues, such as the relationships between overconfidence, confirmation bias, and valuation variation. The results highlight the salience and value of behavioral economics-based analyses in empirical research on real estate valuation.